Nanogel Dressing with Targeted Glucose Reduction and pH/Hyaluronidase Dual-Responsive Release for Synergetic Therapy of Diabetic Bacterial Wounds - Wanhe Luo; Yongtao Jiang; Jinhuan Liu; Samah Attia Algharib; Ali Sobhy Dawood; Shuyu Xie (Gels, 2025)
The hyperglycemic microenvironment in diabetic wounds predisposes them to bacterial infections, sustains chronic inflammation, and hinders therapeutic efficacy. In this study, antibiotic-loaded fast-crosslinked hybrid nanogel wound dressings (florfenicol nanogels) based on Schiff’s base bond were obtained through N, O-carboxymethyl chitosan (N, O-CMCS) and oxidized hyaluronic acid (OHA). The successfully prepared florfenicol N, O-CMCS/OHA nanogels exhibited obvious pH- and HAase-responsiveness release, which allowed it to quickly release florfenicol at infected wounds to exert on-demand antibacterial activity, as well as accelerate diabetic bacterial-infected wound healing. The nanogel dressings showed excellent antibacterial activity by destroying the bacterial cell membrane and wall. More specifically, the glucose oxidase in the dressings can catalyze the breakdown of high-concentration glucose, generating abundant ROS that directly cause cellular damage. According to the results of wound healing, the dressings showed satisfactory anti-inflammatory and therapeutic effects for the full-thickness mouse skin defect wounds. The nanogel dressings are anticipated to be excellent wound dressings to synergistically overcome the theraputic difficulty of diabetic bacterial wounds.